Engineering mechanics - Jayakumar, V (PHI Learning, 2012)
Designed for the first-year undergraduate students of all engineering disciplines, this well-written textbook presents a comprehensive coverage of the fundamental concepts, principles and applications of engineering mechanics in an easy-to-comprehend manner. The book presents an in-depth analysis of various branches of engineering mechanics and the units of measurements. It discusses the system of forces, its characteristics and graphical representation along with composition of coplanar concurrent/non-concurrent forces in a simple but effective style. Using a self-instructive student-friendly approach, the book describes properties of surfaces which cover centre of gravity and moment of inertia. Separate chapters are devoted to a thorough study of friction, kinematics and kinetics of particles. Finally, this book explains the elements of rigid body dynamics.